Minor Salivary Gland Biopsy in Evaluation Algorithm of Sjögren's Syndrome - P. Stanko; Š. Galbavý; D. Macák; T. Feltsan; R. Blahuta (Czech Dental Chamber, 2008)
Authors analysed retrospectively a group of 174 patients (33 men, 141 women) evaluated within years 2004-2006 at the Dept. of Stomatology and Maxillofacial Surgery in Bratislava for suspect primary and secondary Sjögren's syndrom or sicca-like syndrome (patients after treatment of oral cancer were excluded). Biopsies of minor salivary glands from the lower lip were performed in 156 (89.7 %) of cases. By the focus score evaluation finding of two or more focuses on 4 mm2 glandular tissue confirmed the diagnosis of the Sjögren's syndrome only in 27 (17.53 %) of cases, finding of one focus supported the diagnosis in 32 (20.78 %) patients. Fifty four (35.06 %) of the patients had negative findings and in 41 (26.63 %) of the cases there appeared minimal lymphocytic infiltrates by the histopathology. The authors consider the indication of the biopsy before use of other diagnostic tools as incorrect. Site of biopsy intraorally (lip, buccal region) or extraorally (parotid gland) does not influence the result, but more frequent complications should be considered. Biopsy is obligatory by a suspect primary Sjögren's syndrome.